Bone Mineral Density According to Dual Energy X-ray Absorptiometry is Associated with Serial Serum Alkaline Phosphatase Level in Extremely Low Birth Weight Infants at Discharge - Jin Lee; Hyun-Kyung Park; Ja Hye Kim; Yun Young Choi; Hyun Ju Lee (Pediatrics and Neonatology, 2017)
To examine bone mineral density in extremely low birth weight infants at discharge and investigate whether serial measurements of serum alkaline phosphatase (ALP) and phosphate can predict bone mineralization. Methods: The individuals were 70 preterm infants. Serum calcium, phosphate, and ALP were measured at weekly intervals during admission in extremely low birth weight infants (mean gestational age, 25.3±2.1 weeks; birth weight, 812.8±141.1 g). Bone mineral apparent density (BMAD) of the lumbar spine was prospectively evaluated by dual energy X-ray absorptiometry at discharge (n=70). Results: BMAD was classified as poor (< 25th percentile) at < 0.014 g/cm3, fair (25th–75th percentile) at < 0.014–0.021 g/cm3, and good (> 75th percentile) at > 0.021 g/cm3, based on the distribution of BMAD values in infants with noncomplicated courses of prematurity (n=43). In a further multivariate analysis, the number of total parenteral nutrition days, phosphate at 2 postnatal weeks and 3 postnatal weeks, and ALP at 4 postnatal weeks and 5 postnatal weeks had an impact on bone mineral density at the lumbar spine, independent of gestational age and body weight. Peak ALP activities exceeding 650 IU/L revealed low bone mineral density with 80% sensitivity and 64% specificity (AUC, 0.70; p=0.005). Conclusion: Serial measurements of serum ALP and phosphate are associated with decreased bone mineralization by dual energy X-ray absorptiometry at discharge in extremely low birth weight infants.